2021
DOI: 10.1002/jctb.6996
|View full text |Cite
|
Sign up to set email alerts
|

Integration of dynamic growth modeling and hydrodynamics in an internal‐loop split photobioreactor

Abstract: In this study, new high‐quality experimental data for culturing green microalgae Scenedesmus in tubular and cylindrical split airlift photobioreactors were obtained under different operating conditions. The obtained experimental data of culturing microalgae Scenedesmus in a tubular photobioreactor were used for determining the kinetic parameters of the photosynthetic reaction. On the other hand, the culturing of green microalgae in a split airlift photobioreactor was used to measure the microalgae cell traject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
(153 reference statements)
1
5
0
Order By: Relevance
“…This is explained by the fact that a portion of the gas bubbles separates from the liquid phase at the top of the split plate (on the left side) and flows to the right, then to the downcomer area. Other researchers have also reported similar behavior [7,12,20].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…This is explained by the fact that a portion of the gas bubbles separates from the liquid phase at the top of the split plate (on the left side) and flows to the right, then to the downcomer area. Other researchers have also reported similar behavior [7,12,20].…”
Section: Resultssupporting
confidence: 62%
“…The region is made up of three sections, downcomer, degassing, and the region of riser. Thus, in the center of this cylindrical reactor, a dividing plate is installed, forming a passage for the liquid to circulate inside the reactor [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several models describing microalgae response to light have been proposed in the literature, in some cases including investigation of mass transfer [9,10]. Béchet et al [11] suggested classification into three categories according to how the photosynthetic productivity is computed.…”
Section: Introductionmentioning
confidence: 99%
“…In a multiphase system, the phase holdup is described as the volume fraction occupied by the system phase considered [41][42][43][44].…”
Section: Phase Holdupmentioning
confidence: 99%